Dead but dreaming of electric sheep : a novel - Tremblay, Paul (William Morrow, an imprint of HarperCollins Publishers, 2026)
"Meet Julia Flang, a twenty-something former professional gamer, living with her retired uncle, and working two jobs she doesn't like. Out of the blue, her estranged mother, a CFO for one of the world's largest tech companies, offers her a temp job with a payday Julia can't refuse. One sham interview later, she's offered the job: to chaperone a man in a vegetative state from California to the East Coast. But he's not dead dead: he has an AI mind implanted in his head. Meet a middle-aged man who wakes within a disorienting hellscape filled with monstrous grotesqueries. Worse than the fluid, morphing reality in which he's trapped, he has no memory of who he is. He certainly doesn't remember getting the rabbit tattoo on his arm. He only knows that he must find a certain person. Who? He can't remember. Using a cell phone modeled after a video game controller, Julia fumblingly navigates the man she calls 'Bernie' from the company campus and onto planes and through one of the largest airports in America. All the while, the man endures an ever-changing and worsening nightmare that offers clues as to who he was--and who he must track down. And as their two lives intertwine, Julia and Bernie become unlikely allies and fugitives on a collision course with reality."--